Mechanisms of ceramide‐induced COX‐2‐dependent apoptosis in human ovarian cancer OVCAR‐3 cells partially overlapped with resveratrol1. Issue 8 (12th June 2013) - Lin, Hung‐Yun; Delmas, Dominique; Vang, Ole; Hsieh, Tze‐Chen; Lin, Sharon; Cheng, Guei‐Yun; Chiang, Hsiao‐Ling; Chen, Chiao En; Tang, Heng‐Yuan; Crawford, Dana R.; Whang‐Peng, Jacqueline; Hwang, Jaulang; et al.
Abstract Ceramide is a member of the sphingolipid family of bioactive molecules demonstrated to have profound, diverse biological activities. Ceramide is a potential chemotherapeutic agent via the induction of apoptosis. Exposure to ceramide activates extracellular‐signal‐regulated kinases (ERK)1/2‐ and p38 kinase‐dependent apoptosis in human ovarian cancer OVCAR‐3 cells, concomitant with an increase in the expression of COX‐2 and p53 phosphorylation. Blockade of cyclooxygenase‐2 (COX‐2) activity by siRNA or NS398 correspondingly inhibited ceramide‐induced p53 Ser‐15 phosphorylation and apoptosis; thus COX‐2 appears at the apex of the p38 kinase‐mediated signaling cascade induced by ceramide. Induction of apoptosis by ceramide or resveratrol was inhibited by the endocytosis inhibitor, cytochalasin D (CytD); however, cells exposed to resveratrol showed greater sensitivity than ceramide‐treated cells. Ceramide‐treated cells underwent a dose‐dependent reduction in trans‐membrane potential. Although both ceramide and resveratrol induced the expressions of caspase‐3 and ‐7, the effect of inducible COX‐2 was different in caspase‐7 expression induced by ceramide compared to resveratrol. In summary, resveratrol and ceramide converge on an endocytosis‐requiring, ERK1/2‐dependent signal transduction pathway and induction of COX‐expression as an essential molecular antecedent for subsequent p53‐dependent apoptosis. In addition, expressions of caspase‐3 and ‐7 are observed. However, a p38 kinase‐dependent signal transduction pathway and change in mitochondrial potential are also involved in ceramide‐induced apoptosis. J. Cell. Biochem. 114: 1940–1954, 2013. © 2013 Wiley Periodicals, Inc.